Effect of Cryopreserved Cord Blood on Functional State of Dendritic Cells of Rat Skin with Atopic Dermatitis - Koval, Anna K.; Ostankov, Maksim V.; Bondarovich, Nikolay A.; Yampolskaya, Ekaterina Ye.; Ostankova, Lyudmila V.; Goltsev, Anatoly N. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 159